Traffic of a Viral Movement Protein Complex to the Highly Curved Tubules of the Cortical Endoplasmic Reticulum - Lee, Shu-Chuan; Wu, Chih-Hang; Wang, Chao-Wen (Traffic (Copenhagen, Denmark), 2010)
Intracellular trafficking of the nonstructural movement proteins of plant viruses plays a crucial role in sequestering and targeting viral macromolecules in and between cells. Many of the movement proteins traffic in unconventional, yet mechanistically unknown, pathways to localize to the cell periphery. Here we study trafficking strategies associated with two integral membrane movement proteins TGBp2 and TGBp3 of Potexvirus in yeast. We demonstrate that this simple eukaryote recapitulates the targeting of TGBp2 to the peripheral bodies at the cell cortex by TGBp3. We found that these viral movement proteins traffic as an ~1:1 stoichiometric protein complex that further polymerizes to form punctate structures. Many punctate structures depart from the perinuclear endoplasmic reticulum (ER) and move along the tubular ER to the cortical ER, supporting that it involves a lateral sorting event via the ER network. Furthermore, the peripheral bodies are associated with cortical ER tubules that are marked by the ER shaping protein reticulon in both yeast and plants. Thus, our data support a model in which the peripheral bodies partition into and/or stabilize at highly curved membrane environments.